2022
DOI: 10.3389/fnins.2021.820641
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Static and Dynamic Functional Connectivity in Left and Right Temporal Lobe Epilepsy

Abstract: ObjectiveTemporal lobe epilepsy (TLE) can be conceptualized as a network disease. However, the network characteristics in lateralization remain controversial.MethodsIn this study, resting-state functional MRI scans were acquired from 53 TLE patients [22 with left-side TLE (LTLE) and 31 with right-side TLE (RTLE)] and 37 matched healthy controls. We focused on the characteristics of static and dynamic functional connectivity, including static connectivity patterns and topological properties, as well as temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Compared with HC, patients with SHE spend more time in state 2 (predominantly positive connections between networks) and less in state 1. This altered stability in network connectivity demonstrated the fragility of FC in the brain of patients with SHE 28,41 . Besides, the brain was an organ with strong adaptability.…”
Section: Discussionmentioning
confidence: 95%
“…Compared with HC, patients with SHE spend more time in state 2 (predominantly positive connections between networks) and less in state 1. This altered stability in network connectivity demonstrated the fragility of FC in the brain of patients with SHE 28,41 . Besides, the brain was an organ with strong adaptability.…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al (2010) and Amiri et al (2020) have separately demonstrated that the utility of ALFF analysis and graph theory application to brain network analysis might be a potential biomarker to assist in the determination of TLE laterality. Pang et al (Li et al, 2022) found that RTLE patients exhibited more pronounced aberrant connectivity patterns and topological properties revealed by static or dynamic functional connectivity. Consequently, a subgroup analysis is necessary in the future study.…”
Section: Limitationsmentioning
confidence: 89%
“…In a literature search of the aforementioned IBA dynamic indicators, most research on TLE was found to focus on dynamic FC studies ( Jiang et al, 2020 ; Li et al, 2022 ; Pang et al, 2022 ). However, the relevant studies which applied the other dynamic indicators, such as dALFF, dfALFF, dReHo, dDC, dVMHC and dGSCorr, in TLE patients could not be retrieved.…”
Section: Introductionmentioning
confidence: 99%
“…The SMN and VIS represent the perceptual networks and play a critical role in lower-level cognitive processing ( Liu et al., 2015 ). They are together responsible for information communication with the external environment ( Pang et al., 2021 ). Aberrant activity in VIS and SMN has been found both in the resting state and responding to social threat in SAD patients.…”
Section: Discussionmentioning
confidence: 99%